Clinical aspects of Asperger syndrome in the Community of a public university (Research, Society and Development, 2021)
Asperger Syndrome (AS) is a neurodevelopmental disorder that progresses with significant deterioration in the individual's social, occupational and other important activities. People with the syndrome usually have memorization skills and are good at math or science. AS is a recent disease, where there is still controversy about diagnosis and treatment, tending to be underdiagnosed. Objective: To evaluate the presence of clinical aspects of AS among students, technicians and professors at a federal university in the interior of Minas Gerais, Brazil. Methodology: The Australian Scale for AS was applied through an online questionnaire and the score data were analyzed by the ANOVA test and the Pearson correlation test, using the GraphPrism 5.0 statistical program, considering a significance level of p